Global prevalence of hepatitis B or hepatitis C infection among patients with tuberculosis disease: systematic review and meta-analysis - Olaru, Ioana D.; Meier, Mina Beliz; Mirzayev, Fuad; Prodanovic, Nevena; Kitchen, Philip J.; Schumacher, Samuel G.; Denkinger, Claudia M. (EClinicalMedicine, 2023)
Background - There is a substantial overlap in the epidemiology of chronic hepatitis B (HBV), hepatitis C (HCV) and tuberculosis (TB) due to overlapping risk factors. Testing for viral hepatitis is not widely recommended for patients with TB. The aim of this systematic review was to evaluate the global prevalence of chronic viral hepatitis infection among patients with TB. - Methods - MEDLINE, EMBASE, Web of Science, Cochrane Library, African Journals Online, LILACS, and country TB reports were searched for studies published between January 1st, 2011 and June 17th 2021. Random-effects meta-analyses for proportions were conducted to obtain pooled prevalences. The prevalence of chronic HBV/HCV infection among patients with TB was also compared to that in the general population. The protocol was registered on PROSPERO (CRD42021276468). - Findings - This analysis included 127 studies (83 for both HBV and HCV, 28 for HBV only, and 25 for HCV only) and data from 94,936 patients. The global pooled seroprevalence was 5.8% (95% CI 5.0-6.8) for HBs-antigen and 10.3% (95% CI 8.4-12.3) for HCV-antibodies. Pooled prevalence was highest in the WHO African Region for HBV at 7.8% (95% CI 5.2-10.9) and in the WHO European Region at 17.5% (95% CI 12.2-23.5) for HCV. In studies among TB patients who inject drugs, HCV prevalence was 92.5% (95% CI 80.8-99.0). Pooled HCV-antibody seroprevalence among patients with TB was higher than in the general population in all six WHO regions while HBs-antigen seroprevalence was higher in 3/6 regions. - Interpretation - This review highlights the syndemicity of chronic viral hepatitis and TB and suggests that routine testing for hepatitis upon TB diagnosis may be justified. The prevalence of chronic HBV and HCV infections was higher among patients with TB than in the general population. - Funding - This study was study was funded by the Global Tuberculosis Programme, World Health Organization.
Gesehen am 04.08.2023